Dynamic mooring simulation with Code_Aster with application to a floating wind turbine. (1st March 2018) - Antonutti, Raffaello; Peyrard, Christophe; Incecik, Atilla; Ingram, David; Johanning, Lars
Abstract: The design of reliable station-keeping systems for permanent floating structures such as offshore renewable energy devices is vital to their lifelong integrity. In highly dynamic and/or deep-water applications, including hydrodynamics and structural dynamics in the mooring analysis is paramount for the accurate prediction of the loading on the lines and hence their dimensioning. This article presents a new workflow based on EDF R&D's open-source, finite-element analysis tool Code_Aster, enabling the dynamic analysis of catenary mooring systems, with application to a floating wind turbine concept. The University of Maine DeepCwind-OC4 basin test campaign is used for validation, showing that Code_Aster can satisfactorily predict the fairlead tensions in both regular and irregular waves. In the latter case, all of the three main spectral components of tension observed in the experiments are found numerically. Also, the dynamic line tension is systematically compared with that provided by the classic quasi-static approach, thereby confirming its limitations. Robust dynamic simulation of catenary moorings is shown to be possible using this generalist finite-element software, provided that the inputs be organised consistently with the physics of offshore hydromechanics. Highlights: Inclusion of dynamic effects is essential for reliable mooring system design for highly dynamic offshore structures. Open-source finite-element software Code_Aster from EDF R&D is shown to handle mooring dynamics upon correct set-up. Motions and fairlead tensions are validated using existing basin test data from the DeepCwind-OC4 floating wind campaign. Regular and irregular wave cases are compared, showing good agreement between the dynamic numerical and physical model. Mid-high frequency tension components from quasi-static approach are severely underestimated for the considered load cases.